VARIABILITY OF NATIVE TRICHODERMA SPECIES ISOLATED FROM RHIZOSPHERE OF GROUNDNUT (ARACHIS HYPOGEAE L.) IN MANIPUR - RASHMI KH; B. SINHA; PRAMESH KH (The Bioscan, 2015)
The present study was conducted to understand the variability of Trichoderma spp isolated from groundnut rhizosphere from six different groundnut growing areas of Manipur viz., Moirang, Chanung, Ningthoukhong, Andro, Churchandpur and Yambem during kharif 2013 and altogether seven isolates of two different Tricho- derma spp. were isolated, among these, five were identified as T.harzianum, two were T.viride. The radial growth of Trichoderma isolates tested on three different media showed that PDA was found to be the best (8.42 cm). Maximum growth was obtained with isolate TvG2 in all the three media and lowest with TvG7. The growth pattern of T. viride was light green with fluffy growth and produced coconut like aroma in all the three media whereas growth of T. harzianum was fast to very fast without any significant aroma. Anamorphic characters viz., size of phialides, phialospore and conidiophores of all Trichoderma spp were ranges from 3.6–8.5X1.2-3.6μm, 1.5-5.3X1.2-2.8μm and 4.1-35.8X2.1-5.4μm respectively. The biopriming of groundnut seed showed increase in vigour index over control (TvG2- 454.00, TvG1-410.13, control - 222.80). The rhizosphere colonization of the two isolates of Trichodrma spp. were found significantly differences upto 30 days of sowing.